A bioaccessible fraction of parboiled germinated brown rice exhibits a higher anti-inflammatory activity than that of brown rice - Siriporn Tuntipopipat (2018)
© The Royal Society of Chemistry. Parboiled germinated brown rice (PGBR) has been suggested as a functional food because it is relatively rich in a number of nutrients and health promoting compounds. Here we compared the bioaccessibility of several of the bioactive compounds in cooked PGBR and brown rice (BR) by simulating oral, gastric and small intestinal digestion. The uptake and retention of bioactive compounds from a bioaccessible fraction also was determined using Caco-2 human intestinal cells. The anti-inflammatory activity of the bioaccessible fraction from digested BR and PGBR was then assessed with Caco-2 cells that were activated with H2O2 + IL-1β. PGBR had a higher content of GABA, γ-oryzanol, γ-tocotrienol, ferulic acid and p-coumaric acid than BR. The amounts of these compounds transferred to the aqueous fraction during digestion and the quantities accumulated by Caco-2 cells were proportional to those in cooked PGBR and BR. The anti-inflammatory activity of the bioaccessible fraction from digested BR and PGBR was then assessed for Caco-2 cells that were activated with H2O2 + IL-1β. Pre-treatment of the cells with the bioaccessible fractions from PGBR and BR suppressed the secretion of IL-8 and MCP-1 and the ROS content in activated cells. Inhibitory activities were attenuated to a greater extent after cells had been pre-exposed to the bioaccessible fraction from digested PGBR compared to BR. These results suggest that digested PGBR contains and delivers greater amounts of compounds with anti-inflammatory activity to absorptive epithelial cells than digested BR.